THE GUT MICROBIOME AND ITS ROLE IN HUMAN HEALTH - Anna Hawryluk; Katarzyna Urbańska; Adam Żuczek; Kinga Dyndał; Marcelina Broda; Olga Żuczek; Izabela Szczap; Kamil Marzec; Aleksandra Mokrzycka; Patrycja Jędrzejewska-Rzezak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: The human gut microbiome has become the subject of intensive scientific research in recent years due to its significant impact on the body. Disturbances in its composition, called dysbiosis are linked to diseases such as inflammatory bowel disease (IBD), obesity, type 2 diabetes, allergies and neuropsychiatric disorders. This review summarizes current knowledge about the gut microbiome - its composition, functions, research methods, therapeutic options and health impact. Materials and methods: The review was based on an analysis of scientific literature from the PubMed database. The selected publications concerned the composition and development of the microbiome, its function in the pathogenesis of diseases and diagnostic methods and therapeutic strategies. Results: The gut microbiome is a complex ecosystem of bacteria, viruses, fungi and archaea. It develops from the perinatal period depending on delivery mode, feeding, diet, antibiotics, and lifestyle. It ferments undigested components into short-chain fatty acids (SCFA), synthesizes vitamins, modulates immunity and protects against pathogens. Dysbiosis is linked to chronic inflammation "leaky gut" and metabolic, autoimmune and neuropsychiatric diseases. Therapies include probiotics, prebiotics, synbiotics, diet changes, fecal microbiota transplantation (FMT) and new methods such as bacteriophages or precise microbiome editing using CRISPR-Cas technology (a biological system that bacteria and archaea use to defend against viruses). Conclusions: Growing evidence supports the critical role of the gut microbiome in health. Although the links between dysbiosis and disease are clear, direct causality remains uncertain. Future research should identify key microorganisms, develop personalized therapies based on microbiota modulation and ensure the safety of treatments. Properly shaping the microbiome may open new possibilities for preventing and treating chronic diseases.